Synthesis and Characterization of P-PPD-Ph-Conjugated Flame Retardant - Sun, Junzhuo; Zhang, Daohai; Wei, Ke; Tan, Fang; He, Min; Bao, Dongmei; Qin, Shuhao (Frontiers in Chemistry, 2022)
The conjugated flame retardants have rarely been studied. A conjugate flame-retardant 4, 4'-{1″, 4″-phenylene-bis [amino- (10‴-oxy10‴-hydro-9‴-hydrogen- 10‴λ5-phosphaphenanthrene-10″-yl)-methyl]}-diphenol (P-PPD-Ph) was synthesized and added into the polylactic acid (PLA) matrix. The P-PPD-Ph-conjugated flame-retardant structure was tested by FTIR, 1H, and 31P NMR analysis. The thermal and rheological properties of PLA/P-PPD-PH-conjugated flame-retardant composites were investigated. The results showed that P-PPD-Ph-conjugated flame retardant affects PLA/P-PPD-PH-conjugated flame-retardant composites for promoting the formation of a carbon layer when the P-PPD-Ph-conjugated flame-retardant content was 15% and the residual carbon ratio for PLA/P-PPD-PH-conjugated flame-retardant composites increased by 4.2%.